(untitled) (Research, Society and Development, 2020)
Diabetic Ketoacidosis is defined as a complication due to insulin deficiency and is mainly related to Type 1 Diabetes Mellitus. This pathology is considered a medical emergency and requires immediate care, being the cause of death and permanent disability of adolescents; having a sociodemographic influence on its involvement, in developed countries the mortality rate is 2 to 5% and in developing countries it reaches 6 to 24%. The study aims to describe the factors that predispose to diabetic ketoacidosis in adolescents evidenced in scientific publications. It is an integrative literature review with a qualitative approach; the descriptors were consulted through the Health Sciences Descriptors (DeCS) and the Medical Subject Headings (MeSH). Their respective crossings were carried out through the Virtual Health Library Platform and the PubMed portal; using the Boolean operators "AND", "OR". 10,069 publications were identified, of which, after applying the inclusion and exclusion criteria, 14 articles were selected for the sample of this review. Ten (71.4%) were identified at MEDLINE / Pubmed, two (14.3%) at LILACS and two (14.3%) at SCIELO. Regarding the clinical and social aspects, non-adherence to the treatment of diabetes, incorrect treatment and presentation of infectious conditions; the lowest socioeconomic level, families with no history of this pathology, the lowest level of paternal education are predisposing factors for Diabetic Ketoacidosis. For effective interventions, it is important that health teams systematize their work process and actions as recommended, aiming to guarantee health and reduce morbidity and mortality related to the disease.